Improvement of optical signal-to-noise ratio of a high-power pump by stimulated Brillouin scattering in an optical fiber - Marhic, Michel E.; Cholan, Noran Azizan (Optical Society of America, 2014)
We propose and demonstrate improvement of optical signal-to-noise ratio of a highpower pump by saturated stimulated Brillouin amplification of a backward seed in a fiber. A 27-dB improvement was obtained for a 1-W pump.